2014
DOI: 10.1186/2251-6581-13-62
|View full text |Cite
|
Sign up to set email alerts
|

A study of the use of carbamazepine, pregabalin and alpha lipoic acid in patients of diabetic neuropathy

Abstract: BackgroundDiabetic peripheral neuropathy (DPN) is a common, symptomatic, long-term complication of diabetes mellitus. Many of the agents used to treat DN have not been compared with each other. This study was, therefore, undertaken to compare the efficacy and safety of carbamazepine, pregabalin and alpha-lipoic acid in diabetic neuropathy patients.MethodsThis was a prospective, observational study. The patients were categorized into three groups, Group I included those patients who were prescribed carbamazepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…Thus, the analgesic action of pregabalin is also proposed to be the result of impaired trafficking of α2δ1 subunit with a consequent diminished expression of functional calcium channels [133] . Several clinical trials evaluating pregabalin in DNP showed efficacy in the management of this condition [3,134,135] with a number needed to treat (NNT) of 6.3 [125] .…”
Section: Anticonvulsantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the analgesic action of pregabalin is also proposed to be the result of impaired trafficking of α2δ1 subunit with a consequent diminished expression of functional calcium channels [133] . Several clinical trials evaluating pregabalin in DNP showed efficacy in the management of this condition [3,134,135] with a number needed to treat (NNT) of 6.3 [125] .…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…In addition to its analgesic effects, pregabalin presents anxiolytic activity [132,135] and it has a beneficial effect on sleep and quality of life [132] , contributing, therefore, to improve the general condition of the patients. The side effects include dizziness, somnolence, peripheral edema, headache and weight gain [3] .…”
Section: Anticonvulsantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another prospective, observational study showed that after 21 months patients using pregabalin had better improvement in symptoms of diabetic neuropathy in comparison to patients using either carbamazepine and ALA [164] . …”
Section: Clinical Use Of Ala In Diabetesmentioning
confidence: 99%
“…LA, a powerful antioxidant, can inhibit the generation of oxygen free radicals and thus can regulate GSH. This suggested that LA might have certain protective effects against diseases induced by oxygen free radicals (Bhadri et al, 2013;Guo et al, 2014;Patel et al, 2014). Our study demonstrated that Aβ peptides could significantly inhibit the proliferation of C6 cells, while LA could reverse the inhibition effect of Aβ and promote the recovery of cell viability.…”
Section: Discussionmentioning
confidence: 62%